Chrysalis. A Collection of Art by University of Ottawa Medical Students - Aesculapian Society, Faculty of Medicine (Université d'Ottawa | University of Ottawa, 2017)
The University of Ottawa Medical Student Art Show, under the auspices of the Aesculapian Society, is an initiative that celebrates artistic expression as a meaningful method of promoting personal wellness for medical students. This art show is a way to ensure that medical students in all four years can be exposed to the benefits of art-based learning through the creation of reflective art.
Keywords: Chrysalis; medicine; art; student; University of Ottawa